A medieval farmstead at Stauran: Arkeologisk undersökning i Tjeldsund kommune, Troms - Cerbing, Mikael (Tromura, 2026)
Stauran is a long-known farmstead locality situated on the mainland in Tjeldsund municipality, in the northeastern part of Tjeldsundet. The site was partially investigated in 1988–1989, re-registered in 2015, and its final section was examined in 2023 by the Arctic University Museum of Norway. The investigations indicate that a farm settlement was likely established at Stauran sometime around the year 1000 CE. The site consists of several houses that were probably used during different periods. In the lower part of the farm, a large waste deposit was also examined in 2023. A large number of artifacts were collected in 2023, many of which have been precisely dated. Additionally, a significant amount of bones was collected, several of which have undergone osteological analysis. Stauran appears to have been abandoned sometime in the late 13th century and was never re-established as a farm.
Keywords: archaeological excavation; archaeology; farmstead; house; medieval period; osteology